Roles of Phosphoinositides and Their binding Proteins in Parasitic Protozoa. Issue 12 (December 2019) - Cernikova, Lenka; Faso, Carmen; Hehl, Adrian B.
Abstract : Phosphoinositides (or phosphatidylinositol phosphates, PIPs) are low-abundance membrane phospholipids that act, in conjunction with their binding partners, as important constitutive signals defining biochemical organelle identity as well as membrane trafficking and signal transduction at eukaryotic cellular membranes. In this review, we present roles for PIP residues and PIP-binding proteins in endocytosis and autophagy in protist parasites such as Trypanosoma brucei, Toxoplasma gondii, Plasmodium falciparum, Entamoeba histolytica, and Giardia lamblia . Molecular parasitologists with an interest in comparative cell and molecular biology of membrane trafficking in protist lineages beyond the phylum Apicomplexa, along with cell and molecular biologists generally interested in the diversification of membrane trafficking in eukaryotes, will hopefully find this review to be a useful resource. Highlights: PIPs are lipid species with multiple roles in subcellular trafficking, signaling, and cell growth. Parasitic protists employ a variety of PIPs and PIP-binding proteins in both canonical and noncanonical functions. PIP-binding proteins involved in autophagy in model organisms have been co-opted to roles in organelle maintenance and partitioning in several parasitic protist lineages.